مستوي انتشار الأكاديمي لدي التلاميذ المتمدرسين في السنة الثالثة الثانوي - غانم، ابتسام (جامعة محمد الصديق بن يحيى جيجل, 2022)
هدفت الدراسة التعرف على مستوى انتشار التسويف الأكاديمي لدى التلاميذ المتمدرسين في السنة الثالثة ثانوي ومعرفة إن كانت هنالك فروق في مستوى انتشار التسويف الأكاديمي لديهم تعزى للمتغيرات الجنس (ذكور، إناث) التخصص (علوم تجريبية، آداب وفلسفة)، وإعادة السنة النهائية (معيد، غير معيد). ولتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي، حيث طبقت خطواته على عينة قصدية بلغ عددها 56 تلميذة وتلميذا متمدرسين في ثانوية لوصيف رشيد بولاية سكيكدة -الجزائر، خلال السنة الدراسية 2020-2021 م. بعد معالجة البيانات إحصائيا باستخدام المتوسطات الحسابية والانحرافات المعيارية واختبار "ت" لعينيتين مستقلتين بواسطة البرنامج الإحصائي للعلوم الاجتماعية SPSS توصلت الدراسة إلى: - وجود مستوى متوسط لانتشار التسويف الأكاديمي لدى التلاميذ المتمدرسين في السنة الثالثة ثانوي. - عدم وجود فروق في مستوى انتشار التسويف الأكاديمي لدى التلاميذ تعزى لمتغير الجنس. - عدم وجود فروق في مستوى انتشار التسويف الأكاديمي لدى التلاميذ تعزى لمتغير إعادة السنة النهائية. The study aimed to identify the level of spread of academic procrastination among students in the third year of secondary school, and to find out whether there are differences in the level of spread of academic procrastination among them due to the variables of gender (male, female), specialization field (experimental sciences, literature and philosophy), and repeating their final year (a student who repeated the year and a student who passed). To achieve the objectives of this study, the descriptive approach was relied on, as its steps were applied to a chosen sample of 56 students (female and male) study in Lussif Rachid Secondary School in Skikda -Algeria, during the academic year 2020-2021. After processing the data statistically using arithmetic means, standard deviations, and t-test for two independent samples by the statistical program for the social sciences "SPSS", the study concluded that: - There is an average level of spread of academic procrastination among the students in the third year of secondary school. - There are no differences in the level of academic procrastination among the students due to the gender variable. -There are no differences in the level of spread of academic procrastination among students due to the repeating the final year.
Keywords: التسويف الأكاديمي -- التعليم الثانوي